A Policy To Improve The Quality of UMN Alwasliyah Medan and Panca Budi Development University - Sibuea, Bismar; Lubis, Saiful Akhyar; Siahaan, Amiruddin; Ramadhani, Yulia R (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
The purpose of this research is to describe the policies that Pancabudi Development University and UMN Alwasliyah Medan implement, the process by which policies are made, the manner in which policies are implemented, any variations in policy implementation, and the challenges that the institutions face in the field and how they resolve them. The present study employs a qualitative research methodology in conjunction with an empirical policy research strategy. By first outlining each policy at each site, doing an analysis inside each site, and then conducting an analysis between sites, this research used a multisite research design. The study's findings demonstrate that Pancabudi Development University has a policy for quality enhancement. 1) a rule requiring all UNPAB instructors and affiliated parties to promptly adapt to higher education standards without the chancellor's commands 2) Modify the metrics and raise the caliber of the literature produced by the instructors 3) Create a rewards program for instructors who successfully publish in journals approved by SINTA and Scopus. 4) Help instructors with their writing 5) Establish